2015
DOI: 10.1016/j.carbpol.2015.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanocrystals prepared via formic acid hydrolysis followed by TEMPO-mediated oxidation

Abstract: Cellulose nanocrystals (CNCs) as a renewable and biodegradable nanomaterial have wide application value. In this work, CNCs were extracted from bleached chemical pulp using two stages of isolation (i.e. formic acid (FA) hydrolysis and 2,2,6,6-tetramethyl-piperidine-1-oxyl (TEMPO) mediated oxidation) under mild conditions. In the first stage, FA was used to remove hemicellulose, swell cellulose fibers, and release CNCs. The FA could be readily recovered and reused. In the second stage, the CNCs isolated by FA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 205 publications
(124 citation statements)
references
References 42 publications
11
113
0
Order By: Relevance
“…(1) (Yu et al 2013) and crystal size (D hkl ) was estimated using the Scherrer Eq. (2) (Li et al 2015a) shown as follows:…”
Section: Fourier Transform Infrared (Ftir) Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) (Yu et al 2013) and crystal size (D hkl ) was estimated using the Scherrer Eq. (2) (Li et al 2015a) shown as follows:…”
Section: Fourier Transform Infrared (Ftir) Analysesmentioning
confidence: 99%
“…At last, the obtained CNC suspensions (the consistency was about 1 %) were stored in a cold room (4°C) for further treatments or tests. The yields of the obtained products were calculated based on the volume and solid content of the resultant F-CNC suspensions (Li et al 2015a). …”
Section: Formic Acid Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, in order to improve the efficiency of hydrolysis, higher temperature and longer reaction time are necessary because of the weak acidity of organic acid. Li and coworkers reported a two-step strategy to produce CNCs from bleached chemical pulp under mild conditions [80]. In the first stage, formic acid (FA) was used to hydrolyze the amorphous region of cellulose and release CNCs.…”
Section: Organic Acid Hydrolysismentioning
confidence: 99%
“…This possibility is further supported by the recent production of NCC in 42-70% yield from bleached chemical hardwood pulp (silver birch (Betula pendula)) using formic acid in combination with HCl. [33] Despite this information, we began to investigate NFC fabrication using an organic acid process. [30,34] For recent oxalic acid pretreatment of kraft bleached Eucaluptus pulp in combination with disk milling for fabrication of NFC, see ref.…”
Section: Nanocellulosesmentioning
confidence: 99%